"Justice delayed is justice denied": Records management and the travesty of justice in South Africa. (16th November 2015) - Ngoepe, Mpho; Makhubela, Salmon
Abstract : Purpose: – The purpose of this study is to investigate the cases of "delayed and denied" justice that resulted from a lack of or poor record-keeping in the South African courts and police service with a view to encouraging proper records management. Proper records management plays a significant role in supporting the justice system. Records provide the critical evidence that a particular action or transaction took place and can be used as evidence in a court of law. Without reliable and authentic records, government cannot administer justice and, as a result, offenders can be set free while the victims are denied justice. Design/methodology/approach: – Utilising content analysis, this study extracted print media articles (2000-2012) relating to the "records and justice system" from the South African Media database, which is one of the databases hosted by the South African Bibliographic and Information Network. The study selected cases reported in the media to conduct follow-up interviews with a policeman, lawyer and judge to discover the implications of the unavailability of required records in court cases. Furthermore, access was given to three selected cases that were given high profile in the media and these cases were analysed to find out what the final verdict in each case was. Findings: – Results of the study suggest that some criminal cases were withdrawn due to missing dockets or cases not properly registered. In some instances, records were reconstructed, resulting in the travesty of justice. The study concludes by arguing that if records are not accounted for, lawyers, prosecutors and magistrates could dispute the authenticity of records. As a result, justice for victims would be delayed and ultimately denied while the perpetrators are freed. Research limitations/implications: – The findings and recommendations of this study may go a long way in helping courts in South Africa to manage records properly to support the justice system. Furthermore, the study is a useful compilation of the importance of missing records for social purposes. Originality/value: – In an attempt to show the role of records management in the administration of justice in South Africa, this study used a triangulation of data collection tools. This is a new attempt, especially in the South African context. Previous studies in southern Africa only looked at the management of records in supporting justice system.